Quantitative CT metrics are associated with longitudinal lung function decline and future asthma exacerbations: Results from SARP-3 - Krings, James G.; Goss, Charles W.; Lew, Daphne; Samant, Maanasi; McGregor, Mary Clare; Boomer, Jonathan; Bacharier, Leonard B.; Sheshadri, Ajay; Hall, Chase; Brownell, Joshua; Schechtman, Ken B.; Peterson, Samuel; et al. (Journal of allergy and clinical immunology, 2021)
Currently, there is limited knowledge regarding which imaging assessments of asthma are associated with accelerated longitudinal decline in lung function. We aimed to assess whether quantitative computed tomography (qCT) metrics are associated with longitudinal decline in lung function and morbidity in asthma. We analyzed 205 qCT scans of adult patients with asthma and calculated baseline markers of airway remodeling, lung density, and pointwise regional change in lung volume (Jacobian measures) for each participant. Using multivariable regression models, we then assessed the association of qCT measurements with the outcomes of future change in lung function, future exacerbation rate, and changes in validated measurements of morbidity. Greater baseline wall area percent (β = –0.15 [95% CI = –0.26 to –0.05]; P < .01), hyperinflation percent (β = –0.25 [95% CI = –0.41 to –0.09]; P < .01), and Jacobian gradient measurements (cranial-caudal β = 10.64 [95% CI = 3.79-17.49]; P < .01; posterior-anterior β = –9.14, [95% CI = –15.49 to –2.78]; P < .01) were associated with more severe future lung function decline. Additionally, greater wall area percent (rate ratio = 1.06 [95% CI = 1.01-1.10]; P = .02) and air trapping percent (rate ratio =1.01 [95% CI = 1.00-1.02]; P = .03), as well as lower decline in the Jacobian determinant mean (rate ratio = 0.58 [95% CI = 0.41-0.82]; P < .01) and Jacobian determinant standard deviation (rate ratio = 0.52 [95% CI = 0.32-0.85]; P = .01), were associated with a greater rate of future exacerbations. However, imaging metrics were not associated with clinically meaningful changes in scores on validated asthma morbidity questionnaires. Baseline qCT measures of more severe airway remodeling, more small airway disease and hyperinflation, and less pointwise regional change in lung volumes were associated with future lung function decline and asthma exacerbations.